Friends or foes? Migrants and sub-state nationalists in Europe. Issue 8 (20th June 2016) - Jeram, Sanjay; van der Zwet, Arno; Wisthaler, Verena
ABSTRACT: How do sub-state nationalists respond to the growing presence of cultural diversity in their 'homelands' resulting from migration? Sub-state nationalists in Europe, in 'nations without states' such as Catalonia and Scotland, have been challenging the traditional nation-state model for many decades. While the arguments in favour of autonomy or independence levelled by these movements have become more complex, sub-state nationalist movements remain grounded by their perceived national community that is distinct from the majority nation. Migration to the 'homeland' of a sub-state nation, then, presents a conundrum for sub-state elites that we label the 'legitimation paradox': too much internal diversity may undermine the claim to cultural distinctiveness. We engage with three common intervening variables thought to influence how sub-state nationalists confront the 'legitimation paradox': civic/ethnic nationalism, degree of political autonomy, and party competition. Our overarching argument is that none of these factors have a unidirectional or determinate effect on the sub-state nationalism-immigration nexus, which is why the nuanced case studies that comprise this Special Issue are worthwhile endeavours.